Cultural Methods Used by Women Who Give Vaginal Birth to Cope with Birth Labour Pain. - Ozcan, Handan; Samur, Inci; Uzun, Fatma; Sahin, Resul (International Journal of Caring Sciences)
Background: Labour is one of the most severe pain sources known and described today. Many non-pharmacological methods reduce labour pain. Objectives: The study was planned to identify women who delivered vaginally, who did not participate in any birth preparation classes, the ways they coped with birth pain and the traditional methods they used. Methods: The sample consisted of a total of 350 women who agreed to participate voluntarily in the study and have given birth by vaginal delivery after the explanation of the purpose of the study. Required permissions have been obtained. Appropriate statistical analyzes were performed. Results: In the reduction of labour pain, 94.3% of the date eaters, 94.6% of the zam-zam water drinkers, 85.6% of the prayers, 86.1% of those who had massage, 79.4% of the breathing techniques users, 84.4% of those who were supported, 85.1% of the walkers, 87.3% of the worshipers stated that their pain decreased and they psychologically relaxed. Especially in the reduction of the labour pain, women have used methods such as walking, screaming, crouching, showering, massage, breathing exercises, providing calming, warm compress. Conclusion: Women who have used traditional methods have used methods such as praying, controlling their breath, eating a date, drinking zam-zam water, putting Maryam's flower into water, getting support from someone, getting massage, listening to music. It is important to investigate different applications for health according to the cultures and to support patients in this respect.